Glorification of divine love in the works of Alisher Navoi - Namunaxon Xo'jamova Xalidjanovna (Zien Journals, 2022)
this article talks about the poet Alisher Navoi and the glorification of divine love in his works
Keywords: poet; art; Sultan Hussein; philosophical practice